The Legal Vulnerability Model for Same-Sex Parent Families: A Mixed Methods Systematic Review and Theoretical Integration - Siegel, Magdalena; Assenmacher, Constanze; Meuwly, Nathalie; Zemp, Martina (Frontiers in Psychology, 2021)
Globally, parents and children in same-sex parent families are impacted by many laws related to the parental sexual orientation. These laws vary considerably from one country to another, ranging from full legal recognition to criminalization. The psychological consequences of living in an ambiguous or hostile legal climate likely interfere with parental health, family functioning, and child development. However, a systematic evidence synthesis of the pertinent literature and its placement within a broader psychological model are currently lacking. The aims of this review were thus (1) to systematically review qualitative and quantitative evidence on the impact of sexual orientation laws on same-sex parent families in key domains and (2) to place these findings within a broader model informed by minority stress and family theories. Our review was preregistered and conducted in line with PRISMA guidelines. We searched for qualitative, quantitative, and mixed methods studies on the impact of sexual orientation laws on target outcomes (parental health, family functioning, child outcomes) via systematic database search (PubMed, Scopus, Web of Science) and forward-backward searches. Fifty-five studies published between 1999 and 2020 were eligible for inclusion and were synthesized using a data-based convergent synthesis design. Thirteen descriptive and three overarching analytical themes were identified through thematic synthesis. Linking our findings with minority stress and family theories, we propose a novel legal vulnerability model for same-sex parent families. The model posits that legal vulnerability constitutes an increased risk for parental and child health as well as family functioning through individual and shared pathways between family members. Additionally, the model introduces counteractions that families engage in on the personal, familial, and systemic level to mitigate the impact of legal vulnerability, as well as moderators on the contextual, familial, couple, and individual level that modulate this impact. Implications for research and clinical practice are discussed.